1994
DOI: 10.1111/j.1475-097x.1994.tb00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes in relation to a maximal exercise test in patients with fibromyalgia

Abstract: Patients with fibromyalgia often complain of fatigue and pain during exercise and of worsening of pain days after exercise. The aim of the study described here was to determine if abnormal changes in potassium or lactate could be observed during an exercise test in fibromyalgia. Whether an abnormal incline in plasma creatine kinase or myoglobin could be observed days after the test was studied also. Fifteen female fibromyalgia patients and 15 age- and sex-matched controls performed a stepwise incremental maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 17 publications
(13 reference statements)
4
21
0
3
Order By: Relevance
“…Both the lactate threshold and the ventilatory anaerobic threshold were found to be decreased in FMS compared to control subjects [508,509,514], i.e., patients reached anaerobic threshold at lower absolute and relative work levels [514]. However, basal and peak circulating lactate concentrations and lactate levels at exhaustion were similar in patients and controls after various types of exercises [368,508,515]. Some cohorts of FMS patients actually exhibited significantly lower lactate concentrations after exercise, but this was most likely a reflection of lower effort [510,513].…”
Section: Muscle Ischemiamentioning
confidence: 84%
See 2 more Smart Citations
“…Both the lactate threshold and the ventilatory anaerobic threshold were found to be decreased in FMS compared to control subjects [508,509,514], i.e., patients reached anaerobic threshold at lower absolute and relative work levels [514]. However, basal and peak circulating lactate concentrations and lactate levels at exhaustion were similar in patients and controls after various types of exercises [368,508,515]. Some cohorts of FMS patients actually exhibited significantly lower lactate concentrations after exercise, but this was most likely a reflection of lower effort [510,513].…”
Section: Muscle Ischemiamentioning
confidence: 84%
“…It is specifically this accumulation of lactate that has been hypothesized to induce muscle pain [506]. Investigations of these issues have yielded inconsistent results, with some finding lower oxygen uptake (VO2 max) after exercise to volitional exhaustion [507][508][509][510], but others reporting similar VO2 max in patients and controls [393,[511][512][513]. Both the lactate threshold and the ventilatory anaerobic threshold were found to be decreased in FMS compared to control subjects [508,509,514], i.e., patients reached anaerobic threshold at lower absolute and relative work levels [514].…”
Section: Muscle Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin and mineral status. All studies that investigated vitamin B12 (n = 1) [62], folic acid (n = 1) [62], iron (n = 2) [48,50], molybdenum (n = 1) [66], phosphorus (n = 4) [46,49,61,71,72] sodium (n = 3) [42,46,66], and iodine (n = 1) [66], and the majority of studies that investigated potassium (n = 3/4) [42,46,59], and selenium status (n = 4/5) [39,46,66,69] found no statistically significant difference between patients and controls (Table 3). In contrast, all studies that investigated vitamin B1 (n = 1/1) [54], and manganese (n = 1/1) [46], and the majority of studies that investigated vitamin A (n = 2/4) [39,67], found statistically significant lower serum values in patients versus controls.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…However, immediate and longlasting pain, rather than a delayed onset of pain, has been found after both concentric and eccentric muscle contractions in FM20.Furthermore, no difference was found between pain intensities measured both immediately and 24 hours after exercise in the leg that had performed eccentric compared with that performed concentric muscle contractions 20 . The plasma creatine kinase in patients with FM did not differ from that of healthy individuals the following days after exercise 22 …”
Section: Structural Muscle Damagementioning
confidence: 65%